2000
DOI: 10.1053/jhep.2000.8701
|View full text |Cite
|
Sign up to set email alerts
|

Increased hepatocyte turnover and inhibition of woodchuck hepatitis B virus replication by adefovir In vitro do not lead to reduction of the closed circular DNA

Abstract: The aim of this study was to evaluate the inhibitory effect of the nucleotide analogue adefovir on woodchuck hepatitis B virus (WHV) replication and, in particular, to determine whether the pool of covalently closed circular DNA (cccDNA) could be reduced by adefovir treatment in primary cultures of woodchuck hepatocytes isolated from a chronic carrier. Strong reduction of WHV-DNA synthesis (90%) and secretion (up to 98%) was observed with all 3 doses of adefovir used (1, 10, and 100 mol/L), whereas in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 29 publications
5
75
0
1
Order By: Relevance
“…4,5 Woodchuck studies 6,7 and recent clinical trials 8 demonstrated that significant reduction in the cccDNA pool was achieved only after long-term antiviral therapy. As HBV polymerase inhibitors do not have a direct effect on cccDNA formation, the decreased intrahepatic cccDNA levels are supposed to be derived from the lack of sufficient recycling of viral nucleocapsids to the nucleus because of the strong inhibition of viral DNA synthesis in the cytoplasm and less incoming viruses from the blood.…”
Section: Nfection With Hepatitis B Virus (Hbv) Causes Acutementioning
confidence: 99%
“…4,5 Woodchuck studies 6,7 and recent clinical trials 8 demonstrated that significant reduction in the cccDNA pool was achieved only after long-term antiviral therapy. As HBV polymerase inhibitors do not have a direct effect on cccDNA formation, the decreased intrahepatic cccDNA levels are supposed to be derived from the lack of sufficient recycling of viral nucleocapsids to the nucleus because of the strong inhibition of viral DNA synthesis in the cytoplasm and less incoming viruses from the blood.…”
Section: Nfection With Hepatitis B Virus (Hbv) Causes Acutementioning
confidence: 99%
“…Thus, it seems that either cccDNA is not lost at mitosis or the mutant does not replicate any more efficiently than the wild-type virus. Again, it is not known for certain if cccDNA survives mitosis, though some published evidence suggests this is the case [12,55].…”
Section: Forward Mutationmentioning
confidence: 99%
“…1 Due to this peculiar replication mechanism, cccDNA is not a direct target of current antiviral therapies. Experimental evidence from a woodchuck model and clinical trials shows that in the presence of polymerase inhibitors, the cccDNA pool persisted even when viral production was strongly reduced 4,5 and that long-term antiviral therapy is needed to achieve significant decrease of cccDNA levels. [6][7][8] Considering that cccDNA is very stable in the absence of cell division, 5 the development of resistant mutants escaping antiviral therapy may eventually occur.…”
mentioning
confidence: 99%
“…12 A cccDNA decrease was also observed in hepatocytes chronically infected with woodchuck hepatitis virus when cell turnover was induced in vitro by addition of cellular growth factors and viral replication was suppressed by adefovir treatment. 4 Furthermore, identification of cccDNA-free woodchuck hepatocytes containing traces of the infection in form of viral integrations indicated that cccDNA clearance may occur without killing the infected cells. 9 Due to the narrow host range of HBV and limited availability of infection models, little is known about the impact of liver regeneration on cccDNA stability.…”
mentioning
confidence: 99%